Digital Mindset, Technological Self-Efficacy, and Social Media Usage on Entrepreneurial Intention: Mediation of Innovation Capability and Moderation of Digital Literacy - Nurfaizal, Yusmedi (Universitas Airlangga, 2025)
Objective: This study investigates the influence of digital mindset, technological self-efficacy, and social media usage on entrepreneurial intention among digital business students, with innovation capability as a mediating variable and digital literacy as a moderating variable. It clarifies how digital competences and innovation jointly shape entrepreneurial aspirations in an educational context. Design/Methods/Approach: A quantitative research design was applied with data from 250 undergraduate students in digital business programs across several universities. A stratified proportional random sampling technique ensured campus representation. Data were analyzed using SmartPLS4 through the PLS-SEM approach, including measurement and structural model assessment, mediation moderation analysis, and control variables (gender and campus). Findings: The results reveal that digital mindset, technological self-efficacy, and social media usage significantly influence entrepreneurial intention both directly and indirectly through innovation capability. Innovation capability plays a mediating role, while digital literacy strengthens the relationship between innovation capability and entrepreneurial intention. All proposed hypotheses were supported, indicating the robustness of the model. Originality/Value: This study contributes to the growing body of knowledge on digital entrepreneurship education by integrating digital mindset, self-efficacy, and social media usage into a mediation–moderation framework. It extends the Technology Acceptance Model, the Resource-Based View, and Social Capital Theory by demonstrating how innovation capability and digital literacy shape entrepreneurial intention in the context of students in emerging economies. Practical/Policy implication: The findings suggest that higher education institutions should design curricula that integrate digital competences, experiential learning, and innovation-based projects to foster entrepreneurial aspirations. Educators are advised to leverage social media platforms and digital tools in teaching, while policymakers should create supportive ecosystems that strengthen digital literacy and innovation capability among students to prepare them for entrepreneurial engagement in the digital economy.